Values and Science: An Argument for Why They Cannot Be Separated. Issue 2 (2nd April 2016) - Reeves, Josh
ABSTRACT: A distinction between facts and values is often assumed when people in the modern West talk about science. The biologist Stephen Gould, for example, famously argued that religion covers questions of meaning and moral value, but science deals with empirical facts. This paper challenges the traditional fact/value distinction by questioning the presuppositions about science upon which it depends. It begins by describing the origins of the fact/value distinction in the Scientific Revolution and then gives three reasons for the inseparability of facts and values in scientific inquiry, drawing upon themes from the "practice turn" in recent scholarship on the sciences.